Nutrient deprivation induces α-synuclein aggregation through endoplasmic reticulum stress response and SREBP2 pathway - Jiang, Peizhou; Gan, Ming; Lin, Wen-Lang; Yen, Shu-Hui C. (Frontiers in Aging Neuroscience, 2014)
Abnormal accumulation of filamentous α-synuclein (α-syn) in neurons, regarded as Lewy bodies(LBs), are a hallmark of Parkinson disease (PD). Although the exact mechanism(s) underlying LBs formation remains unknown, autophagy and ER stress response have emerged as two important pathways affecting α-syn aggregation. In present study we tested whether cells with the tetracycline-off inducible overexpression of α-syn and accumulating α-syn aggregates can benefit from autophagy activation elicited by nutrient deprivation, since this approach was reported to effectively clear cellular polyglutamine aggregates. We found that nutrient deprivation of non-induced cells did not affect cell viability, but significantly activated autophagy reflected by increasing the level of autophagy marker LC3-II and autophagic flux and decrease of endogenous α-syn. Cells with induced α-syn expression alone displayed autophagy activation in an α-syn dose-dependent manner to reach a level comparable to that found in non-induced, nutrient deprived counterparts. Nutrient deprivation also activated autophagy further in α-syn induced cells, but the extent was decreased with increase of α-syn dose, indicating α-syn overexpression reduces the responsiveness of cells to nutrient deprivation. Moreover, the nutrient deprivation enhanced α-syn aggregations concomitant with significant increase of apoptosis as well as ER stress response, SREBP2 activation and cholesterolgenesis. Importantly, α-syn aggregate accumulation and other effects caused by nutrient deprivation were counteracted by knockdown of SREBP2, treatment with cholesterol lowering agent—lovastatin, or by GRP78 overexpression, which also caused decrease of SREBP2 activity. Similar results were obtained from studies of primary neurons with α-syn overexpression under nutrient deprivation. Together our findings suggested that down-regulation of SREBP2 activity might be a means to prevent α-syn aggregation in PD via reducing cholesterol levels